Idiopathic granulomatous mastitis with erythema nodosum: Is it a variant of clinical presentation indicating treatment resistance? A retrospective cohort study - GÜLLÜOĞLU, MAHMUT BAHADIR (Blackwell Publishing Inc., 2020)
Idiopathic granulomatous mastitis (IGM) rarely occurs with erythema nodosum (EN) as a systemic finding. However, the impact of their coexistence on disease severity and response to steroids has not been investigated yet. Patients diagnosed with IGM between September 2014 and October 2018 were divided into two groups according to the presence or absence of EN during the first admission retrospectively. The IGM was more severe in patients with EN as it was presented more often as bilateral and diffuse involvement of the breast. Findings of mastitis did not resolve with steroids in 50% of this group. Repetitive excisions and mastectomy with reconstructions were required to control the disease. Coexistence of EN and IGM was found to be related to bilateral and aggressive involvement, which could be associated with insufficient response to steroids. Associated patients should be informed in terms of the aggressive course, and surgery can be highlighted as a first-line treatment. © 2020 Wiley Periodicals LLC
Keywords: erythema nodosum; Granulomatous mastitis; response to steroids